Tolerogenic dendritic cells and negative vaccination in transplantation: from rodents to clinical trials - Moreau, Aurelie; Varey, Emilie; Beriou, Gaelle; Hill, Marcelo; Delbos, Laurence; Segovia, Mercedes; Cuturi, Maria-Cristina (Frontiers in Immunology, 2012)
The use of immunosuppressive (IS) drugs to treat transplant recipients has markedly reduced the incidence of acute rejection and early graft loss. However, such treatments have numerous adverse side effects and fail to prevent chronic allograft dysfunction. In this context, therapies based on the adoptive transfer of regulatory cells are promising strategies to induce indefinite transplant survival. The use of tolerogenic dendritic cells (DC) has shown great potential, as preliminary experiments in rodents have demonstrated that administration of tolerogenic DC prolongs graft survival. Recipient DC, Donor DC, or Donor Ag-pulsed recipient DC have been used in preclinical studies and administration of these cells with suboptimal immunosuppression increases their tolerogenic potential. We have demonstrated that autologous unpulsed tolerogenic DC injected in the presence of suboptimal immunosuppression are able to induce Ag-specific allograft tolerance. We derived similar tolerogenic DC in different animal models (mice and non-human primates) and confirmed their protective abilities in vitro and in vivo. The mechanisms involved in the tolerance induced by autologous tolerogenic DC were also investigated. With the aim of using autologous DC in kidney transplant patients, we have developed and characterized tolerogenic monocyte-derived DC in humans. In this review, we will discuss the preclinical studies and describe our recent results from the generation and characterization of tolerogenic monocyte-derived DC in humans for a clinical application. We will also discuss the limits and difficulties in translating preclinical experiments to theclinic.